2016
DOI: 10.1021/jacs.6b04550
|View full text |Cite
|
Sign up to set email alerts
|

Conformations of Prolyl–Peptide Bonds in the Bradykinin 1–5 Fragment in Solution and in the Gas Phase

Abstract: The dynamic nature of intrinsically disordered peptides makes them a challenge to characterize by solution-phase techniques. In order to gain insight into the relation between the disordered state and the environment, we explore the conformational space of the N-terminal 1-5 fragment of bradykinin (BK[1-5](2+)) in the gas phase by combining drift tube ion mobility, cold-ion spectroscopy, and first-principles simulations. The ion-mobility distribution of BK[1-5](2+) consists of two well-separated peaks. We demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 91 publications
1
59
1
Order By: Relevance
“…Bradykinin binds to its receptors in an open geometry where all the Pro 2,3,8 are in the trans conformational structure. Recently, Clemmer's group deconvoluted several conformational structures of BK in different solution composition by using IMS‐MS and established that cis ↔ trans isomerization of prolyl‐peptide bonds is key for different conformations . The interaction of BK with different metal cations viz., alkali, alkaline, and transition metals, was investigated extensively by using tandem MS along with DFT calculations to determine their respective binding site.…”
Section: [Bradykinin‐(n‐1)h + Ncui] and [Bradykinin‐(2n‐1)h + Ncuii];mentioning
confidence: 99%
“…Bradykinin binds to its receptors in an open geometry where all the Pro 2,3,8 are in the trans conformational structure. Recently, Clemmer's group deconvoluted several conformational structures of BK in different solution composition by using IMS‐MS and established that cis ↔ trans isomerization of prolyl‐peptide bonds is key for different conformations . The interaction of BK with different metal cations viz., alkali, alkaline, and transition metals, was investigated extensively by using tandem MS along with DFT calculations to determine their respective binding site.…”
Section: [Bradykinin‐(n‐1)h + Ncui] and [Bradykinin‐(2n‐1)h + Ncuii];mentioning
confidence: 99%
“…[22][23][24] Further, IM-MS can be used to prepare samples for gas-phase IR spectroscopy. [25][26][27][28][29] Here ions are simultaneously mass-tocharge (m/z) selected by MS and specific oligomers are geometrical size selected by IMS. This is in contrast to experiments where only m/z selection is used which can suffer from signal overlap between a cluster and its larger counterpart, which, for example, have twice the mass and twice the charge.…”
mentioning
confidence: 99%
“…For instance, Warnke et al 14 demonstrated that combining IM-MS and infrared multiple photon dissociation (IRMPD) spectroscopy reveals two distinct protomers of benzocaine, where depending on the protonation site (N or O), a unique N-H and O-H stretch frequencies appear. Similarly, Voronina et al 28 utilised IM-MS and cold-ion spectroscopy to study the bradykinin fragment (BK [1][2][3][4][5] 2+ ) ions elucidating cis-trans and trans-cis conformations for the more compact conformer and kinetically trapped trans-trans configuration for the larger conformer, highlighting the cis-trans isomerization of the peptide bonds during the desolvation process. In both cases, IM-MS data was supplemented with gas-phase IR experiments which in turn were supported by high-level calculations to assign potential in vacuo species.…”
Section: Mason-schamp Equation Whereas Travelling Wave Im-ms (Twims-mentioning
confidence: 99%